Ligularia fischeri Extract Protects Against Oxidative-Stress-Induced Neurotoxicity in Mice and PC12 Cells - Choi, Soo Jung; Kim, Jae Kyeom; Suh, Soo Hwan; Kim, Cho Rong; Kim, Hye Kyung; Kim, Chang-Ju; Park, Gwi Gun; Park, Cheung-Seog; Shin, Dong-Hoon (Journal of medicinal food, 2014)
Alzheimer's disease (AD) is pathologically characterized by the presence of amyloid plaques in brain and the overproduction of amyloid beta (Aβ), leading to learning and memory impairment and intense oxidative stress. In this study, the protective effect of Ligularia fischeri extract was investigated using PC12 cells. L. fischeri extract attenuated hydrogen-peroxide-induced DNA fragmentation in cells. In vivo behavioral tests were performed to examine the effects of the extract on amyloid-β peptide₁₋₄₂-induced impairment of learning and memory in mice. A diet containing the extract increased alternation behaviors in the Y-maze test and step-through latency of passive avoidance task. Moreover, we found that consumption of the extract decreased lipid peroxidation in a biochemical study of brain tissue in mice. High-performance liquid chromatography was used to identify the active compounds in the extract. These results suggest that L. fischeri extract could be protective against Aβ-induced neurotoxicity, possibly due to the antioxidative capacity of its constituent, 3-O-caffeoylquinic acid.